BREACH OF PERFORMANCE IN PHOTOGRAPHY SERVICES: THE CLIENT DOES NOT PAY THE FEES AGREED IN THE CONTRACT BASED ON THE CIVIL CODE AND LAW NO. 8 OF 1999 CONCERNING CONSUMER PROTECTION - Syafrizal Syafrizal; Azmiati Zuliah; Andi Maysarah (NOMOI Law Review, 2026)
This article examines the legal consequences of non-payment in photography service agreements in accordance with the Indonesian Civil Code (KUHPerdata) and the Consumer Protection Law (UU No. 8/1999). The objective of this study is to examine different legislative frameworks that safeguard photographers against client non-payment and to evaluate the effectiveness of legal remedies in resolving these disputes. The research employed a qualitative methodology, collecting data through semi-structured interviews with attorneys, photographers, and clients, in addition to analyzing documents such as contracts, judicial decisions, and relevant statutes. The discussion pertains to the concept of "wanprestasi," which signifies the breach of a contract, as outlined in KUHPerdata. It also discusses how the Consumer Protection Law safeguards individuals against fraudulent corporate conduct. The study concludes that both the Civil Code and the Consumer Protection Law serve as essential safeguards for photographers, as they provide legal mechanisms to enforce contracts and obtain compensation for damages. Mediation and arbitration are also two alternative methods recommended for efficiently and cost-effectively resolving payment disputes. The paper emphasizes the significance of incorporating legal protections and dispute resolution mechanisms within photography contracts to ensure that services are compensated equitably and punctually.